Delegation Of Medical Tasks And Delivery Of Information By Doctors To Nurses Based On Law Number 38 Of 2014 Concerning Nursing - Herry Febriadi (Scholar Center, 2022)
Delegation is the delegation of authority in the process of transferring duties and responsibilities given by doctors to nurses, program implementers, or services to carry out certain tasks within a certain time. Legal actions in the medical world are carried out with the delegation of authority and informed consent in the provision of health care. Health is a human right that is recognized and protected by the 1945 Constitution of the Republic of Indonesia. Based on the results of the study, it is understood that the application of the law regarding the legal force of delegation of authority and informed consent must be carried out correctly following the Standard Operating Procedures (SOP) that have been established. there are, in addition, medical and non-medical already know and understand the rules and consequences of the actions to be taken in connection with the delegation of authority and the provision of informed consent.